Fractionated Concurrent Exercise throughout the Day Does Not Promote Acute Blood Pressure Benefits in Hypertensive Middle-aged Women - Azevêdo, Luan M.; Souza, Alice C. de; Santos, Laiza Ellen S.; Miguel dos Santos, Rodrigo; Fernandes, Manuella O. M. de; Almeida, Jeeser A.; Pardono, Emerson (Frontiers in Cardiovascular Medicine, 2017)
Hypertension is a chronic disease that affects about 30% of the world’s population and the physical exercise plays an important role on its non-pharmacological treatment. Anywise, the dose-response of physical exercise fractionation throughout the day demands more investigation, allowing new exercise prescription possibilities. Therefore, this study aimed to analyze the acute blood pressure (BP) kinetics after 1h of exercises and the BP reactivity after different concurrent exercise (CE) sessions and its fractioning of hypertensive middle-aged women. In this way, 11 hypertensive women voluntarily underwent three experimental sessions and one control day (CS). In the morning (MS) and night (NS) sessions, the exercise was fully realized in the morning and evening, respectively. For the fractionized session (FS), 50% of the volume was applied in the morning and the remaining 50% during the evening. The MS provided the greatest moments (p≤0.05) of post-exercise hypotension (PEH) for systolic BP (SBP) and highest reduction of BP reactivity for SBP ( 44%) and diastolic BP (DBP) ( 59%) compared to CS (p≤0.05). The findings of the present study have shown that MS is effective for PEH to SBP, as well as it promotes high quality of attenuation for BP reactivity, greater than the other sessions.